Chemosensitivity testing of ovarian cancer using the histoculture drug response assay: sensitivity to cisplatin and clinical response. Issue 3 (1st April 2005) - Nakada, S.; Aoki, D.; Ohie, S.; Horiuchi, M.; Suzuki, N.; Kanasugi, M.; Susumu, N.; Udagawa, Y.; Nozawa, S.
Abstract : Despite cytoreductive surgery and chemotherapy, the prognosis of advanced ovarian cancer is still poor. Predicting the chemosensitivity of tumors might improve the outcome. Therefore, we investigated the clinical value of the histoculture drug response assay for ovarian cancer. Tumor specimens were cultured for 7 days on collagen gel sponge in medium containing cisplatin, and the 50% inhibitory concentration was determined by the 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyltetrazolium bromide assay. Then the in vitro sensitivity to cisplatin was compared with the clinical response and survival. Apoptosis of tumor cells was also investigated. Among 173 ovarian cancer patients, 164 were evaluable by the assay, and 29 patients had measurable lesions for which the clinical response could be determined. The 5-year survival rate was significantly higher in patients with chemosensitive tumors than in those with chemoresistant tumors when the cutoff value was set at a 50% inhibitory concentration of 25 μg/mL and the accuracy of the assay was 82.8% (24/29). As chemosensitivity to cisplatin became greater, the number of apoptotic cells also increased. This chemosensitivity assay may help predict the clinical response to cisplatin-based chemotherapy, thus improving the survival of ovarian cancer patients.